PENGGUNAAN FAIR VALUE ATAU HISTORICAL COST DALAM NILAI AKTIVA BERSIH PADA AKUNTANSI INVESTASI REKSA DANA - UMAR ISSA ZUBAIDI (Media Bisnis, 2012)
At the moment, in indonesia; the usage of mutual fund’s net asset value measurement which is refers to mark to market is still limited. Mostly, it is using historical cost. In fact net asset value of mutual funds that invested on stocks and obligations, which is daily published on mass media, is not as high as shown. It is caused of the value of obligations that lower than historical cost. Since net asset value is not using fair market value or market value, it inflicted a loss upon the investors. According to mutual fund regulation that released by bapepam and psak, the investment manager required to use fair market value or present value for net asset value measurement